Migrant Networks and Foreign Direct Investment - Javorcik, Beata S.; Ozden, Caglar; Spatareanu, Mariana; Neagu, Cristina (2012)
Although there exists a sizeable literature documenting the importance of ethnic networks for international trade, little attention has been devoted to studying the effects of migrants on foreign direct investment (FDI). The presence of migrants can stimulate FDI by promoting information flows across international borders and by serving as a contract enforcement mechanism. This paper investigates the link between the presence of migrants in the US and US FDI in the migrants' countries of origin, taking into account the potential endogeneity concerns. The results suggest that US FDI abroad is positively correlated with the presence of migrants from the host country. The data further indicate that the relationship between FDI and migration is stronger for migrants with tertiary education.